2015
DOI: 10.1039/c5ay00342c
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and selective liquid chromatography mass spectrometry method for simultaneous estimation of anti-diabetic drugs inhibiting DPP-4 enzyme in human plasma: overcoming challenges associated with low recovery and sensitivity

Abstract: DPP-4 inhibitors (gliptins) have shown a better glycaemic control even in more feeble cases such as elderly people, patients with high cardiovascular and hypoglycaemic risk and individuals with renal impairment. However, the plasma concentrations of selected drugs has to be estimated to correlate those results with various uncertainties during clinical studies. A simple and sensitive LC-QTOF/MS method was developed and validated to measure the human plasma concentrations of vildagliptin, saxagliptin, sitaglipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Because the UPLC system withstands higher pressures, it is compatible with stationary phases with a reduced particle size and length, which generates high chromatographic efficiency in a shorter run time. Only two other studies have employed UPLC systems for the quantification of oral antidiabetic agents in plasma [39, 54], but only five analytes were analyzed in each study, from just one [54] and two therapeutic classes [39]. …”
Section: Resultsmentioning
confidence: 99%
“…Because the UPLC system withstands higher pressures, it is compatible with stationary phases with a reduced particle size and length, which generates high chromatographic efficiency in a shorter run time. Only two other studies have employed UPLC systems for the quantification of oral antidiabetic agents in plasma [39, 54], but only five analytes were analyzed in each study, from just one [54] and two therapeutic classes [39]. …”
Section: Resultsmentioning
confidence: 99%
“…The methods included in this systematic review were validated according to the criteria established by the "Guidance for Industry - Bioanalytical Method Validation" by US FDA [3] (16 records) [9,12,15,[20][21][22][23]27,29,30,[32][33][34][38][39][40], "Harmonized Tripartite Guideline" by ICH [73] (four records) [16,17,36,38], "RDC 27/2012 -Minimum Requirements for Validation of Bioanalytical Methods" by ANVISA [5] (one record) [37], "The Fitness for Purpose of Analytical Methods" by Eurachem [98] (one record) [7], "Requirements for Initial Assay Validation and Publication in Journal of Chromatography B" by Wolfgang Lindner and Irving W. Wainer [99] (one record) [26], "Requirements for the Validation of Analytical Methods" by the Society of Toxicological and Forensic Chemistry [100] (one record) [18]; "Validation of New Methods" by Peters, Drummer and Musshoff, 2007 [101] (two records) [13,18] and "MS Identification Guidelines in Forensic Toxicology" by Australian/New Zealand Specialist Advisory Group in Toxicology [102] (one record) [13]. Although the EMA has a specific guideline for bioanalytical method validation, none of the records declared to have used it as guidance.…”
Section: Bioanalytical Methods Validationmentioning
confidence: 99%
“…The majority of the reported methods are used in clinical applications (Zeng et al, , 2010Nirogi et al, 2008;Hess et al, 2011;Bonde et al, 2013;Burugula et al, 2013;Reddy et al, 2015;Scherf-Clavel and Högger, 2015) compared with preclinical applications (Yao et al, 2011;Gananadhamu et al, 2012;Patel et al, 2014). Shantikumar et al (2015) reported an LC-QTOF/MS method for the determination of five gliptins (vildagliptin, saxagliptins, sitagliptins, linagliptins and teneligliptin) in clinical application. Zeng et al (2006) reported a high-turbulence liquid chromatography coupled to mass spectrometry (HTLC-MS/MS) method to quantify MK-0431 in human plasma.…”
Section: Hplc Coupled With Ms/ms Detectionmentioning
confidence: 96%
“…Sitagliptin was extracted from the DBS card using a mixture of 90% ACN and 10% formic acid to get maximum recovery. A rapid-resolution HD column was used for the separation of five gliptins in human plasma by Shantikumar et al (2015) with a gradient elution. Recovery was low in glass tubes because of nonspecific binding compared with polypropylene tubes; it was optimized initially in the method development phase and the recovery was found to be >90% for all of the analytes.…”
Section: à80°cmentioning
confidence: 99%